Perceived Parenting Styles and its Impact on Imposter Phenomenon and Life Satisfaction in Youth - Amoli Kapur; Smriti Sethi (International Journal of Education Sciences, 2026)
Parenting styles play an important role in forming an individual’s perception of self, thinking process as well as their overall well-being. However, there is limited research on how different methods of parenting influences imposter feelings and life satisfaction. The aim of the study was the understand the relationship between perceived parenting styles and its impact on imposter phenomenon and life satisfaction among youth population. Data from a sample of 100 participants between the ages of 15 to 24 years was collected for this research and were asked to fill the Perceived Parenting Style Scale, Clance IP Scale and Satisfaction with Life Scale. Results showed that perceived parenting style significantly influences both the imposter phenomenon and life satisfaction of youth. Authoritative parenting showed to be negatively correlated with imposter feelings (r = -0.468) while being positively correlated with life satisfaction (r= 0.427). Authoritarian parenting, on the other hand, showed a positive relationship with imposter phenomenon (r = 0.449) and a negative relationship with life satisfaction (r = -0.426). Lastly for Permissive parenting style, correlation with imposter feelings showed to be positive (r = 0.428) and negative with life satisfaction (r = -0.194). Regression analysis further confirms that perceived parenting styles significantly predict both imposter phenomenon and life satisfaction of the individual with authoritative parenting showing the highest positive impact on both variables.
Keywords: Authoritative parenting; Imposter Phenomenon; Perceived Parenting Styles; life satisfaction; youth